José Enrique Martínez. La huella de la herida. Sobre la poesía de José Luis Puerto. León, Ediciones Universidad de Salamanca / Eolas & Menoslobos (Ursa Maior), 2022, 258 pp., ISBN: 978-84-18718618 - Panero García, María Pilar (Anales de Literatura Española, 2023)
Reseña: José Enrique Martínez. La huella de la herida. Sobre la poesía de José Luis Puerto. León, Ediciones Universidad de Salamanca / Eolas & Menoslobos (Ursa Maior), 2022, 258 pp., ISBN: 978-84-18718-61-8.